ANALISIS PEMODELAN DAN SIMULASI EVAKUASI TSUNAMI MENGGUNAKAN INTEGRASI AGENT-BASED MODELING, 3-D MODELING, DAN ARTIFICIAL INTELLIGENCE (STUDI KASUS: DESA PANGANDARAN DAN DESA PANANJUNG, INDONESIA) - Nurul Aini, Atik
Pangandaran Village and Pananjung Village have tourist attractions and high economic activities. This area has a history of the Mw 7,7 earthquake in 2006, and according to the latest research, belongs to the area that has the potential to experience an Mw 8,7-9 earthquake that triggers a large tsunami. This study aims to determine the effect of the location and number of Temporary Evacuation Sites (TES), mode of evacuation, and time of departure on the effectiveness of evacuation, and to test the feasibility of refugee preferences in determining evacuation destinations. The selection of an effective evacuation model is carried out through a multi-scenario simulation approach. In its application, the Agent-Based Modeling and Simulation method, which can also bridge geoscience and social science, is used for evacuation modeling and simulation. Artificial Intelligence plays a role in modeling the behavior of large groups by simulating the behavior and interactions of individual agents. Simulations were carried out with 13 scenarios based on variations in the types of TES - namely existing TES, alternative TES (TES recommended by the government, but not yet inaugurated), and recommended TES (TES proposed in this study based on Location-Allocation Modeling method)-, mode evacuation, and departure time. The digital infrastructure is built using 3-D Modeling which is integrated with the simulation environment. The modeling results show that the recommended TES can increase the efficiency and effectiveness of evacuation, while the alternative TES does not. Refugee preferences are considered inadequate and require further education. The use of bicycle, motorbike, and car evacuation modes, in general, can increase the effectiveness of evacuation, but it is only optimum in the first 16 minutes. Refugees are recommended to evacuate immediately after feeling signs of a tsunami or receiving an early warning. The solution to the congestion is to widen the road or direct agents to other, more streamlined evacuation routes. The results of this study are expected to assist practitioners in designing effective tsunami evacuation plans.